THE EFFICACY OF Toona sureni (Bl.) merr LEAF EXTRACT ACROSS DIFFERENT CONCENTRATIONS IN MANAGING TOBACCO CUTWORM (Spodoptera litura F.) INFESTATIONS - Saputra, Yudikat; Brotodjojo, Raden Roro Rukmowati (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Control of S. litura by farmers still depends on the use of synthetic pesticides which are believed to be practical. Toona sureni is a plant that has potential as a vegetable insecticide. This research was carried out at the Plant Protection Laboratory, Faculty of Agriculture, UPN